Feasibility, indications and complications of SCIP flap for reconstruction after extirpative surgery for vulvar cancer. Issue 3 (March 2022) - Gentileschi, Stefano; Caretto, Anna Amelia; Servillo, Maria; Stefanizzi, Gianluigi; Alberti, Caterina; Garganese, Giorgia; Fragomeni, Simona Maria; Federico, Alex; Tagliaferri, Luca; Moroni, Rossana; Scambia, Giovanni
Summary: Introduction: Surgical therapy for vulvar cancer involves wide defects that often require flap-based reconstruction. The goal of the reconstruction is fast wound healing with low donor site morbidity. Materials and methods: This is a retrospective observational cohort study in which we reviewed all patients who underwent surgery for vulvar cancer followed by reconstruction using the Superficial Circumflex Iliac Artery Perforator (SCIP) flap between 2015 and 2020. The primary outcome measure of this investigation was the incidence of wound complications. The secondary outcomes were the surgical indications in terms of establishing the anatomical subunits involved in the resection that made us choose this flap for reconstruction. This study adheres to the STROBE guidelines. Results: Thirty-two patients were included; in two cases, the flap was performed bilaterally for a total of 34 SCIP flaps. The mean age of patients was 70.6 ± 8.6 years, and the mean BMI was 26.8 ± 4.7. The SCIP flap was always feasible. The mean flap size was 128.8 ± 74.3cm 2 . Three patients showed wound complications. In every patient, the defect involved the vulva, perineum and inguinal area; in 18 patients, the mons pubis was also involved. The mean follow-up was 30 months. During the follow-up, six patients died, and four showed local or nodal cancer relapse. Conclusion: Our results suggest that the advantages of SCIP flap for the reconstruction of vulvoperineal defects secondary to vulvar cancer surgery include low complication rate, minimal donor site morbidity, quick dissection, proximity of donor and recipient sites, possibility to harvest large skin islands of variable thickness and chimeric flaps.